Conflict Management of Hot Spring Forest Tourism Objects in Pendalian IV Koto District, Rokan Hulu Regency - Jahro, Aqila Yaumil Ginati Jihan; Nasution, Mimin Sundari (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
Nowadays, social conflicts in society are increasingly varied and take many forms, even tending to shift and develop into long-standing acts of violence that we can even feel directly. The increase in forest utilization as an industrial sector has triggered conflicts related to licensing, violation of regulations, and illegal exploitation of forest areas by communities. The complexity of problems arising from the forest utilization process is also caused by the inconsistency of policy makers, especially local governments that act as the authority that issues forest area management permits This research was conducted in hot spring forest tourism in Pendalian IV Koto sub-district, Rokan Hulu Regency. The purpose of this study is to determine the Conflict Management of Tourism Objects in Hot Water Village, Pendalian IV Koto District, Rokan Hulu Regency and to determine the inhibiting factors in solving Conflict Management of Tourism Objects in Pendalian IV Koto District, Rokan Hulu Regency. The method used in this study is qualitative descriptive. Data collection is carried out using observation, interviews and documentation.Data analysis using the Moles and Huberman model is data reduction, data presentation and drawing conclusions / verification. The results of this study show collaboration, accommodation, dominance, avoidance and compromise in resolving conflict management in hot spring forest tourism in Pendalian IV Koto sub-district, Rokan Hulu Regency.